Wax hearts: seeking the antiquity of cardiac pathology - Henriques de Gouveia, Rosa; Santi, Raffaella; Ballestriero, Roberta; Galassi, Francesco; Carvalho, Lina; Nesi, Gabriella (Polish Journal of Pathology, 2021)
Wax models of normal and diseased organs were formerly essential medical teaching tools. The ceroplastic heart models from two 19th century pathology museums at the Universities of Florence (n = 8) and Coimbra (n = 10) were analysed. The Florentine collection comprised congenital malformations as well as infectious and inflammatory disorders. The Coimbra waxworks included congenital defects, cardiac hypertrophy and dilation, valvular pathology and cardiac adiposity. This study focuses on heart diseases and teaching resources in European university hospitals during the 19th century. It also highlights the importance of wax models in medical education both then and today, in an era of informatics and digital photography.